Evolutionary plasticity of segmentation clock networks - Krol, Aurélie J; Roellig, Daniela; Dequéant, Mary-Lee; Tassy, Olivier; Glynn, Earl; Hattem, Gaye; Mushegian, Arcady; Oates, Andrew C; Pourquié, Olivier (Development (Cambridge), 2011)
The vertebral column is a conserved anatomical structure that defines the vertebrate phylum. The periodic or segmental pattern of the vertebral column is established early in development when the vertebral precursors, the somites, are rhythmically produced from presomitic mesoderm (PSM). This rhythmic activity is controlled by a segmentation clock that is associated with the periodic transcription of cyclic genes in the PSM. Comparison of the mouse, chicken and zebrafish PSM oscillatory transcriptomes revealed networks of 40 to 100 cyclic genes mostly involved in Notch, Wnt and FGF signaling pathways. However, despite this conserved signaling oscillation, the identity of individual cyclic genes mostly differed between the three species, indicating a surprising evolutionary plasticity of the segmentation networks.